CONCEPT OF IMPROVING MANAGEMENT EFFICIENCY OF OIL ENTERPRISES UNDER TRANSFORMATION OF THE DIGITAL ECONOMY - Abduhakim Yuldashev (The Conference Hub, 2025)
This article covers the concept of improving the management efficiency of oil enterprises. Also, effective management of the enterprise and rational solution of the existing problem, and the main goals in the field of production were widely studied and analyzed. In addition, the main functions of management systems and the influence of modern concepts and technologies on the process of enterprise management are widely evaluated. In addition, the concept of integrated supply management, which emerged in the last decade, has been widely analyzed as the concept of related flows such as "design - purchase - production - distribution - sales - service" in the integrated business structure. The connection between ISO 9000 and the concept of TQM is scientifically based on the need to combine orders from different suppliers into one delivery, instead of delivering small batches from different suppliers on time. Conclusions and suggestions on improving the management efficiency of oil enterprises are given.
Keywords: digital economy, transformation, digital technologies, oil enterprises, management efficiency, effective management of the enterprise, Concept of ISO 9000 and TQM, enterprise strategy.